Islamic Micro-Finance Programme and its Impact on Rural Poverty Alleviation (International Journal of Banking and Finance, 2010)
Bangladesh launched a shariâ€™ah based micro-finance programme in 1995 under the Rural Development Scheme to uplift the overall socioeconomic standards of rural poor. It covered 0.52 million group members, 94% of whom are females. This paper presents findings on this experiment using 1,020 responses in a sample survey. Result showed that a significant of clients have improved their religious observations such as prayers and fasting. Results of the econometric models showed that household income, productivity of crops and livestock, expenditure and employment increased significantly due to the influence of changed behaviour and availability of micro-finance. Clients stated that the micro-investment had provided better organisation of their economic activities. Finally, the Islamic micro-investment programme appears to spur more ethical and economically desirable behaviour leading to poverty alleviation.